Novel hyper-crosslinked polymer anode for lithium-ion batteries with highly reversible capacity and long cycling stability. (10th August 2018) - Li, Zhaopeng; Zhong, Weihao; Cheng, Ao; Li, Zhenghui; Li, Liuqing; Zhang, Haiyan
Abstract: Organic materials with high natural abundance, low price as well as environmental friendliness have been considered as proper alternatives to replace inorganic electrodes. However, it is still challengeable for exploiting novel organic materials incorporating highly stable framework in electrolyte, optimized nanostructure and large lithium storage capacity. In the present work, hyper-crosslinked polystyrene (HPS) nanospheres are fabricated by combination of emulsion polymerization and subsequent Friedel-Crafts reaction. The obtained HPS has abundant oxygen-containing functional groups for reversible lithium ions storage reactions, uniform spherical morphology along with well-developed porous structure to minimize transfer distance of lithium ions, rigid macromolecular frameworks to resist the dissolution of electrolyte. Therefore, HPS presents promising potential as electrode in lithium ion battery. The initial discharge and charge capacities of HPS can reach 533 and 262 mAh g − 1, respectively, and a stable capacity of 356 mAh g −1 is delivered after repeated charge-discharge for 100 times at 0.2 A g −1 . Even cycled for 1000 times at 2 A g −1, the capacity remains 222 mAh g −1 . Graphical abstract: Image 1 Highlights: HPS is prepared by combining emulsion polymerization and Friedel-Crafts reaction. HPS has rigid molecular framework, well-defined micropores and anchored functional groups. HPS exhibits an impressive lithium storage performance.